Blacks in the military and beyond - Harris, G. L. A. (Lexington Books, 2019)
"African Americans have long used the military for gaining legitimacy and the ultimate path to citizenship. Blacks in the Military and Beyond chronicles their tumultuous journey from slavery through the present, extending the history to significant factors in determining whether or not serving in the military has indeed advantaged Blacks."